Improving the Quality of Public Services through Innovation of Online Complaints Based on the Wargaku Application - Diana Hertati (Journal La Sociale, 2023)
Communities have broad access to submit complaints to public service providers. However, there are still problems with public complaint services, so efforts to improve public service delivery are needed. The Surabaya City Government made a breakthrough through the innovative Wargaku application as a responsive and informative complaint service. The purpose of this study is to analyze the Improving the Quality of Public Services through the Innovation of Online Complaints Based on the Wargaku Application at the Surabaya City Communication and Information Service. This type of qualitative descriptive research and data collection techniques with interviews, observation, and documentation. Data analysis uses an interactive data analysis model from Miles and Huberman, namely: collection, presentation and condensation of data, and conclusion. The research results show that Improving the Quality of Public Services Through Innovation of Online Complaints Based on the Wargaku Application at the Surabaya City Communication and Information Service can run optimally as evidenced by the relative advantages that provide convenience and community satisfaction; suitability by updating and perfecting Wargaku innovations, the complexity is different because people have unequal abilities and knowledge; the possibility of trying it has gone through trials and socialization of the Wargaku application program to the public and is easy to observe, the complaint application made is not much different from before.